The Pediatric Fluid Cytology: A 2-year experience of a tertiary care pediatric center of North India - Singh, Savitri; Nath, Devajit; Tiwari, Neema (Asian Journal of Medical Sciences, 2021)
Background: Body fluid analysis containing exfoliated cells in effusion may reveal information about neoplastic and non-neoplastic etiology. Most important indication of fluid cytology is to look for malignant cells. CSF examination is another investigation performed routinely in all tertiary care centers in addition to other body fluids examined. Aims and Objective: The aim of the study was to examine the body fluids for cytological examination in diagnosis, prognostic and therapeutic tool for management of pediatric cases. Materials and Methods: Retrospective data analysis of 170 fluid cytology cases taken from departmental data archive of pediatric cases (0-18 years) from Jan 2018-Dec 2019 was tabulated observation was done by 2independent pathologists. The smears were stained with Romanowsky stains and specialized stains of AFB and Rhodamine auramine, MPO, PAS and PAP as per requirement. Results: There were higher number of male (n=99, 58.23%) compared to female (n=71, 41.76%). The commonest fluid cytology received was the CSF (n=150, 88.23%) with 77 samples presenting with significantly high TLC for age (using standard age analysis parameters). The diagnosis was grouped into the Neoplastic and Non neoplastic category. The non-neoplastic category was further divided into infective where most common was viral pleocytosis (n=50, 48 Viral lymphocytic pluecytosis, 1case rubella positive CSF, 1 Primary HLH with viral infection) followed by TB(n=10, 6 pleural, 2 CSF, 2 Peritoneal), bacterial (n=07, microbiology culture was done) and TORCH, Rubella with plasmacytosis (n=01). Another non-neoplastic category was of inherited disease where single case of Griscelli’s syndrome was diagnosed showing hemophagocytosis on CSF examination. Neoplastic Cytology was seen in 07 cases where all the cases were hematolymphoid malignancies. Conclusion: This study concludes that fluid cytology is a useful diagnosis, prognostic, therapeutic tool in diagnosis and management of pediatric cases.